The Political Economy Perspective of Forest Governance Responding REDD+ in Indonesia - Pungky Widiaryanto (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2020)
Reducing Emissions from Deforestation and Forest Degradation (REDD+) has become important for Indonesia because this mechanism will provide financial benefits and it adheres to the Indonesian commitment to participate in climate change mitigation. However, a weak forest governance system and lack of transparency have undermined Indonesia’s goals to reduce deforestation and to manage and distribute the compensation appropriately. The idea of transformational change to reform Indonesian forest governance might be hindered by path dependency that has become entrenched within the Indonesian government. This paper, therefore, attempts to analyze path dependency of Indonesian forest governance and to examine the implication of path dependency in the development of REDD+ in Indonesia. Using the political economy lens, the diagnosis of path dependency is determined if there are positive feedbacks for the Ministry of Forestry, as the leading agency in the administration of Indonesian forests, to maintain the status quo. This paper shows that there are four positive or reinforcing feedbacks for the Ministry of Forestry: (1) vested interests for utilizing the forests as an income source, (2) network effects from managing the forest resources, (3) sunk costs invested to strengthen the institution, and (4) inclusiveness of the institution in managing the forests. This paper also highlights that path dependency within the Ministry of Forestry causes a complexity in the REDD+ debate in Indonesia, particularly regarding which institutional arrangement will best implement REDD+. On the other hand, this paper shows that various policies and activities related to REDD+ could break path dependency.